Strategic Public Relations for Strengthening Public Trust in Government - Kurniawan, Agus; Wijoyo, Suparto (Universitas Prasetiya Mulya, 2025)
This study examines the role of public relations in building public trust in Indonesia's public sector. Using the PRISMA-based Systematic Literature Review (SLR) method, the findings indicate that strategic communication and transparency play a crucial role in shaping a positive governmental image. Digital innovations, such as online complaint platforms, enhance transparency and public engagement. Theoretically, this study reinforces the concept of public relations as a strategic tool for strengthening government legitimacy. Moreover, the findings have managerial implications, recommending a more transparent and participatory communication strategy to foster public trust and improve the effectiveness of government policies.